Women in the Political Landscape: A Study on the Roles of Female Legislators in East Nusa Tenggara Province, Indonesia - Rex Tiran; Diana S.A. Natalia Tabun; Rouwland Benyamin; Yohanes Fisher Keon (Mengeja Indonesia Publisher, 2023)
Amidst the prevailing patriarchal culture that dominates various life dimensions, particularly in politics, women's political representation emerges as a beacon of change. Women often face multifaceted socio-political challenges, necessitating them to invest more resources and effort than their male counterparts to make their mark in politics. This research examines the roles and contributions of female legislators in the NTT Provincial DPRD for the 2019-2024 tenure, particularly in aligning with the interests of political parties and the broader categorization of women in legislative bodies. The strategies employed to allocate positions to women are diverse, reflecting their aspirations to enhance their influence and access in politics. These aspirations are anchored in the desire to bolster the capacities of women and youth in political spheres. Emphasizing the significance of economic, social, and political capacities, this study underscores the need for women to possess financial resources, robust social networks, and political acumen to navigate and thrive in the political landscape.